Performance Assesment by Using Behaviorally Anchor Rating Scale and Management by Objective in PT. X - Hastawati Chrisna Suroso; Tifanny Fa'iza Ashari (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
As the competition in industry are getting higher day by day, it is felt necessary to improve employee performance. This is because employees are the key for business actors in the company to achieve the goals desired by the company. At PT. It is felt that this needs to be investigated to find the factors that hinder the failure of the company's achievements. Therefore, it is felt that the Behaviorally Anchor Rating Scale (BARS) method can help solve problems by combining working behavior and worker personality. Apart from that, the Management by Objective (MBO) method will also be used to support the completion of the BARS method so that an assessment category that is less effective is obtained to continue looking for the root of the problem. The result of this research was that the average factor of the BARS method was found with the lowest value being Obedience of 3.8 in the effective category. Meanwhile, the company's two main goals are Analysis of Company Goals and Analysis Division Goals with the findings that inventory management must be the main focus of employees in the company